Comprometimento endotelial, recuperação funcional e efeitos da ventilação não invasiva em pacientes hospitalizados: uma contribuição para as populações COVID-19 e DPOC exacerbada - Heubel, Alessandro Domingues (2023)
Endothelial dysfunction influences in multiple disease conditions, including COVID-19 and exacerbation of chronic obstructive pulmonary disease (ECOPD). In COVID-19, although the endothelium plays an important role in the worsening and complications of the disease, little is known about the characteristics that contribute to endothelial dysfunction during acute viral infection. In patients with ECOPD, while noninvasive ventilation (NIV) is a frequently used tool in the management of respiratory failure, the effects of this therapy on endothelial function are not known. Furthermore, in addition to vascular dysfunction, ECOPD hospitalized patients tend to have decreased exercise tolerance, which may persist for months. In this context, little is known about the role of muscle strength in the recovery of exercise capacity. Therefore, this PhD thesis is composed of 3 studies that aimed to elucidate the presented knowledge gaps. Study 1 – Objective: To identify determinants of endothelial dysfunction in patients hospitalized with acute COVID-19. Methods: Cross-sectional study including 109 patients hospitalized with COVID-19 in noncritical status. Clinical data (age, sex, comorbidities and medications) and body mass index (BMI) were obtained. Laboratory tests included serum hemoglobin, leukocytes, lymphocytes, platelets, C-reactive protein, ferritin, D-dimer, and creatinine. Physical function was assessed using a handgrip dynamometer. Endothelial function was assessed non-invasively using the flow-mediated dilation (FMD) method. Results: The sample average age was 51 years, 51% were male, and the most frequent comorbidity was obesity (62%). Univariate analysis showed association of lower FMD with higher BMI, hypertension, use of oral antihypertensive, higher blood levels of creatinine, and larger baseline artery diameter. After adjusting for confounders, the multivariate analysis showed BMI as the major factor associated with FMD (95% CI -0.26, -0.11; P < 0.001). Other factors associated with FMD were baseline artery diameter (95% CI -1.77, -0.29; P = 0.007) and blood levels of creatinine (95% CI -1.99, -0.16; P = 0.022). Conclusion: BMI was the main factor associated with endothelial dysfunction in non-critically hospitalized COVID-19 patients, which may explain one of the pathways in which obesity may increase the risk for severe disease. Study 2 – Objective: Quasi-experimental study including 21 ECOPD patients that were assessed in a hospital ward setting from 24 to 48 hours after admission. NIV was applied using a ventilator with bilevel pressure support. Before and after NIV protocol, patients were evaluated regarding endothelial function (FMD method) and arterial blood gas analysis. Other baseline evaluations included clinical and anthropometric data, and laboratory tests. Results: The total group showed a significant improvement in FMD as a result of NIV effect (P = 0.010). While arterial carbon dioxide and oxygen were not altered, oxygen saturation increased after NIV (P = 0.045). The subgroup comparison of responders (FMD ≥ 1%) and non-responders (FMD < 1%) showed significant baseline differences in BMI (P = 0.019) and predicted forced expiratory volume in one second (FEV1) (P = 0.007). In univariate and multivariate analyses, both BMI and FEV1 were determinant for endothelial response to NIV. Conclusion: NIV acutely improves endothelial function in hospitalized ECOPD patients. Overweight and disease severity may represent important characteristics for the magnitude of vascular response. Study 3 – Objective: To assess whether respiratory and peripheral muscle strength influence recovery of exercise capacity in patients hospitalized due to ECOPD. Methods: Observational prospective study including 27 ECOPD patients (aged 69 ± 7 years, 56% male). The following assessments were performed within 24 to 72 hours of hospital admission: (i) respiratory muscle strength, measured by maximal inspiratory and expiratory pressures (MIP and MEP); (ii) peripheral muscle strength, assessed by handgrip and quadriceps muscle strength; and (iii) exercise capacity, measured by 6-min walking distance (6MWD). The 6MWD was reassessed 30 days later to determine the recovery of exercise capacity. Results: After 30 days, while 63% of the patients showed clinically important improvement in the 6MWD (recovery ≥ 30 m), 37% showed no change (recovery < 30 m). During hospital stay, the non-recovered group had lower quadriceps muscle strength compared to the recovered group (15 ± 5 vs. 22 ± 6 kgf; P = 0.006), with no significant difference for MIP, MEP and handgrip strength. Only quadriceps muscle strength was associated with recovery of exercise capacity (r = 0.56; P = 0.003). Conclusion: ECOPD patients with quadriceps muscle weakness during hospitalization have poor recovery of exercise capacity after 30 days. This finding suggests the importance of early rehabilitation to improve quadriceps strength and accelerate functional recovery after ECOPD. Final considerations and future directions: Given the findings, we conclude: (1) Obesity is the condition that most contributes to endothelial dysfunction during acute COVID-19. Although this finding suggests one of the pathways for severe COVID-19 in obese patients, we consider it essential that longitudinal studies investigate whether this greater impairment of endothelial function represents a worsening of clinical outcomes; (2) NIV acutely improves endothelial function in patients with ECOPD. Although this knowledge indicates a new therapeutic perspective for the NIV use, future investigations should address the modulating mechanisms of this response, as well as verify whether this acute benefit translates into improved clinical outcomes; (3) In ECOPD patients, decreased quadriceps strength during hospitalization is associated with worse recovery of exercise capacity after 30 days. This finding highlights the importance of considering early pulmonary rehabilitation, starting during hospitalization. However, evidence on this subject is still insufficient and high-quality clinical studies are needed.